Market shocks and professionals’ investment behavior – Evidence from the COVID-19 crash - Huber, Christoph; Huber, Jürgen; Kirchler, Michael (Journal of Banking & Finance, 2021)
We investigate how the experience of extreme events, such as the COVID-19 market crash, influence risk-taking behavior. To isolate changes in risk-taking from other factors, we ran controlled experiments with finance professionals in December 2019 and March 2020. We observe that their investments in the experiment were 12 percent lower in March 2020 than in December 2019, although their price expectations had not changed, and although they considered the experimental asset less risky during the crash than before. This lower perceived risk is likely due to adaptive normalization, as volatility during the shock is compared to volatility experienced in real markets (which was low in December 2019, but very high in March 2020). Lower investments during the crash can be supported by higher risk aversion, not by changes in beliefs.